Assembly of vascular smooth muscle cells in 3D aggregates provokes cellular quiescence - Jäger, Marius Andreas; Torre, Carolina de la; Arnold, Caroline; Hecker, Markus; Feldner, Anja; Korff, Thomas (Experimental cell research, 2020)
Three-dimensional (3D) cell culture conditions are often used to promote the differentiation of human cells as a prerequisite for the study of organot…
Available online: 16 December 2019
Gesehen am 24.03.2020